SIGHT SINGING SEBAGAI STRATEGI PEMBELAJARAN INSTRUMEN PIANO DI PRODI PENDIDIKAN MUSIK ISI YOGYAKARTA - Suryati, Suryati; Widodo, Tri Wahyu (Institut Seni Indonesia Yogyakarta, 2020)
Sight Singing is the ability to read the notation and immediately sing the tune in accordance with the melody on the sheet music. Sight Singing is the activity of singing with solmisasi or movabel